Solitary pancreatic metastasis from breast cancer: case report and review of literature - Apodaca-Rueda, Márcio (2019)
CONTEXT: Pancreatic metastases from primary malignant tumors at other sites are rare, constituting about 2% of the neoplasms that affect the pancreas. Pancreatic metastasis from breast cancer is extremely rare and difficult to diagnose, because its clinical and radiological presentation is similar to that of a pri-mary pancreatic tumor. CASE REPORT: A 64-year-old female developed a lesion in the pancreatic tail 24 months after neoadjuvant therapy, surgery and adjuvant radiation therapy for right-side breast cancer (ductal carcinoma). She un-derwent distal pancreatectomy with splenectomy and left adrenalectomy, and presented an uneventful outcome. The immunohistochemical analysis on the surgical specimen suggested that the lesion origi-nated from the breast. CONCLUSION: In cases of pancreatic lesions detected in patients with a previous history of breast neo-plasm, the possibility of pancreatic metastasis should be carefully considered.